Membumikan Ushul Fiqh: Kajian Terhadap Definisi, Objek Pembahasan, dan Urgensi Mempelajarinya di Era Kontemporer - Najwa Fakhira Hisbuddin; Fiantika Armanda; M. Rayhan Idil Fitrah A; Kurniati Kurniati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Ushul fiqh, as a branch of Islamic law, has a significant role in establishing laws based on the main sources of the Koran and Sunnah. The aim of this research is to explain the definition of ushul fiqh comprehensively and explore and identify the main objects of discussion in ushul fiqh and their relevance to contemporary issues. The research method used is library research with a qualitative approach. The result of this research are that Ushul Fiqh is a very important science for Muslims to understand Islam comprehensively and accurately, and to be able to apply it in everyday life. Studying Ushul Fiqh in the contemporary era is very important for various reasons, such as the era of globalization and modernization, the emergence of many schools of thought and ideology, and the need to understand and apply Islam comprehensively and accurately.